Development of Student Worksheets Based on Project Based Learning on Green Chemistry Materials at SMAN 2 Gerung - Dina Rahmatin; Jeckson Siahaan; Sunniarti Ariani (FKIP University of Mataram, 2026)
This research is a development research or Research and Development (R&D) which aims to produce Student Worksheets (LKPD) based on Project Based Learning (PjBL) which are categorized as feasible and practical regarding green chemistry material. The type of research used is Research and Development (R&D) which refers to the 4D model (define, design, develop, disseminate). Validation of the content of LKPD based on PjBL was carried out by two Chemistry Education lecturers and one Chemistry subject teacher at the high school level. The results of the study showed that the validity value obtained using the Aiken's V Index was 0.92 in the very valid category. The level of practicality was measured through student responses to LKPD based on PjBL. The results of the analysis of student responses were in the very practical category with a practicality percentage of 86%. Based on these results, it can be concluded that LKPD Based on PjBL on green chemistry material that was developed is feasible and practical to be used in learning because it has met the valid and practical categories.